TELAAH TENTANG REKOMENDASI OMBUDSMAN TERHADAP FRAUD PERBANKAN - Yasin, Muhammad Rus’an (Katalogis, 2016)
This was a normative research. The problem in this thesis were “1) How is legal standing on Ombudsman recommendation in solving people report?. 2) In scheme of related authority, how is the quality of Ombudsman authority in solving banking Fraud ?. The research aims to: 1) understand the limitation of Ombudsman authority toward banking Fraud happening to BUMN banking and BUMD. 2) understand legal standing of Ombudsman authority to refund to the reporter. The conclusions are: First, banking fraud is maladministration and included in illegal action. Second, Ombudsman recommendation power has been acknowledged by . It is because it already stipulated normatively in Legislation either at Act 38 UU No. 37 of 2008, Act 36 article (2) and (3) UU No. 25 of 2009, or in Act 351 UU No. 9 of 2015. Third, the related authority in solving report by Ombudsman and OJK are included in Act 7 and 8 No. 37 of 2008 and Act 28 and 30 UU No. 21 of 2011. Fourth, the authority limitation is stipulated in Act 5 Ombudsman Regulation of the Republic of Indonesia No. 2 of 2009 and Act 41 at POJK No. 1/POJK.07/2013. Finally, the author advised as follow: First, Financial Service Authority (FSA) must revise Act 41 POJK No. 1/POJK.07/2013. Second, Ombudsman should revise Act 1 UU No. 37 of 2008. Third, Ombudsman and Financial Service Authority (FSA) should build institutional coordination that prioritizes the reporters’ interest. Fourth, in line with Ombudsman recommendation of banking fraud, then, Financial Service Authority must do it.